Effects of process parameters on morphologies of titanium carbide powder by thermal plasma treatment. (22nd January 2020) - Zeng, Sihui; Xiao, Meng; Liu, Xiaoqing; Wu, Yaosha; Li, Kefeng; Qiu, Zhaoguo; Zeng, Dechang
Abstract: High sphericity titanium carbide (TiC) powders with uniform distribution and favorable dispersity were obtained by thermal plasma treatment. By optimizing the process parameters, the spheroidization rate of TiC powders is almost 100%. During solidification process, a transformation from typical dendrite structure to cellular structure microstructure occurs with the increase of feeding speed. It ascribes to the decrease of heat absorbed from plasma torch, resulting in decreasing constitutional undercooling and improving solidified interface stability. Consequently, it promotes the formation of cellular structure.